Efektivitas Modul Pusat Informasi dan Konseling tentang Seks Bebas pada Siswa SMA Surabaya - Ella Novita Sari; Sri Widati (Universitas Airlangga, 2016)
Surabaya is one of the city that has a number of free sex in adolescents. One of the activities of BKKBN is Pusat Informasi and Konseling Remaja (PIK), which one of its activities is using a module of adolescent reproductive health, sexuality and adolescent problems as a media of information and education for adolescents about the menace of sex behavior as the eff ort to mitigate and reduce the number of free sex and it to conduct the activities to reduce and prevent adolescent problems, which commonly called TRIAD KRR that consists of drug problems, HIV-AIDS, and free sex. SMA Surabaya is one of the schools that had 3 cases of free sex in 2012. The aim of this study was to determine the eff ectiveness of the module of PIK on adolescent reproductive health, sexuality and free sex of adolescents in changing the attitudes of the students in one of the high school in Surabaya about free sex. This research is a study with one group pretest posttest design were carried out on 80 students were selected. The statistical test used was paired sample T test. The results showed that the level of respondents’ attitudes decreased, which were the pre-test (p = 50.3500) and post-test (p = 50.0625) and it was not signifi cant, which means there was no diff erence between the pre-test and post-test (p = 0.659). The module had not been effective in improving the attitude of students in one of high school in Surabaya on reproductive health, sexuality, and free sex of adolescents.